2022
DOI: 10.37708/psyct.v15i1.622
|View full text |Cite
|
Sign up to set email alerts
|

Case Study of Relaxation and Counterconditioning Therapy for Misophonia: A Conditioned Aversive Reflex Disorder

Abstract: This article presents a case study of conceptualization of misophonia as a conditioned aversive reflex disorder consisting of a physical (e.g., muscle) reflex elicited by the misophonic trigger stimulus and subsequent emotional, physiological, and behavioral responses. This case describes a successful behavioral treatment of a middle-aged woman who was disabled by severe misophonia. The treatment included identifying the initial physical reflex, progressive muscle relaxation, and counterconditioning the initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(27 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Additionally, spontaneous recovery has been reported in connection to treatments that reduced the IPR ( Dozier, 2015b ). Given that spontaneous recovery is a well-documented characteristic of conditioned reflexes ( Catania, 2013 ), these findings support Pavlovian conditioning as the origin of the IPR ( Dozier, 2015a , 2015b , 2015c , 2022 ).…”
Section: Methodssupporting
confidence: 65%
See 4 more Smart Citations
“…Additionally, spontaneous recovery has been reported in connection to treatments that reduced the IPR ( Dozier, 2015b ). Given that spontaneous recovery is a well-documented characteristic of conditioned reflexes ( Catania, 2013 ), these findings support Pavlovian conditioning as the origin of the IPR ( Dozier, 2015a , 2015b , 2015c , 2022 ).…”
Section: Methodssupporting
confidence: 65%
“…Patients’ IPR responses reported by Dozier (2015b) were often experienced without emotional distress, and participants in another study often reported having a physical sensation but no emotional response or fight-or-flight precursors ( Dozier and Morrison, 2017 ), indicating that the physical response and the emotional response can be dissociated. Furthermore, another patient perceived tensing her jaw and fists to be her emotional/physiological response to triggers ( Dozier, 2022 ). However, with testing, she determined her IPR was jaw tensing, and clenching her fists and jaw was part of her general physiological arousal or anger response.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations